Study of rainfall-runoff relationship using hydrological modelling system (HEC-HMS) for Lipis River Basin, Pahang - Wan Nurfatin, Wan Zainulabidin (2016)
In this study, Hydrologic Engineering Center – Hydrologic Modeling System (HECHMS) is used to determine the rainfall-runoff relationship of Lipis River, Pahang. HECHMS is software use in analyzing, planning, and simulating the process of rainfall and runoff. HEC-HMS 4.0 is used in this study to simulate discharge for Lipis River. This study uses rainfall data and stream flow data from January 2008 to December 2014. The data needed is from eleven rainfall stations and one stream flow station in Lipis River catchment area. The analysis result of the data is depends on the parameter used in HEC-HMS. Snyder Unit Hydrograph and SCS Unit Hydrograph are the method use in this study. The parameters include standard lag, peaking coefficient and lag time. The results of simulation can be generated in form of hydrograph, summary table, and time series table. Root Mean Square Error, RMSE is used to show the relationship of the observed and the simulated flow. If the RMSE value is lesser, it would indicate that the variables are positively linear related. During evaluation of model, the best value RMSE for Snyder UH method is 11.63m3/s while for SCS UH method is 13.148m3/s. It shows that the simulated models were fit with the observed data and proves that the HEC-HMS is suitable to predict and analyze rainfall-runoff relationship in Lipis River.